Alterations of Oral Microbiota in Chinese Patients With Esophageal Cancer - Zhao, Qiaofei; Yang, Tian; Yan, Yifan; Zhang, Yu; Li, Zhibin; Wang, Youchun; Yang, Jing; Xia, Yanli; Xiao, Hongli; Han, Hongfeng; Zhang, Chunfen; Xue, Weihong; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Emerging evidences support that oral microbiota are associated with health and diseases of esophagus. How oral microbiota change in Chinese patients with esophageal cancer (EC) is unknown, neither is the biomarker role of them. For an objective to understand alterations of oral microbiota in Chinese EC patients, we conducted a case-control study including saliva samples from 39 EC patients and 51 healthy volunteers. 16S rDNA genes of V3-V4 variable regions were sequenced to identify taxon. Relationship between oral flora and disease was analyzed according to alpha diversity and beta diversity. Resultantly, the Shannon (p=0.2) index and the Simpson (p=0.071) diversity index were not significant between the two groups. Yet we still found several species different in abundance between the two groups. For the EC group, the most significantly increased taxa were Firmicutes, Negativicutes, Selenomonadales, Prevotellaceae, Prevotella, Veillonellaceae while the most significantly decreased taxa were Proteobacteria, Betaproteobacteria, Neisseriales, Neisseriaceae, Neisseria. In conclusion, there are significant alterations in abundance of some oral microbiome between the EC patients and the healthy controls in the studied Chinese participants, which may be meaningful for predicting the development of EC, and the potential roles of these species in the EC development deserve further studies.